An Adaptive and Distributed Traffic Management System for Vehicular ad-hoc Networks - Gomides, Thiago S.; Guidoni, Daniel L. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2021)
The economic and environmental impacts caused by traffic congestion have become a cause for concern in urban centers. Improvements in the city's road infrastructure for minimizing these impacts are expensive and take time to be executed. In this scenario, Traffic Management Systems (TMSs) emerge as efficient and technological alternatives to tackle vehicular traffic issues. This work proposes a TMS based on vehicular communication to improve vehicular traffic ﬂow in dense urban centers. The proposed work aims to study the following TMS issues: (i) how to estimate traffic jams; (ii) propose proactive and reactive information sharing protocols; (iii) propose an adaptive traffic sharing information that has less impact on the network with more information available and (iv) real-time and periodical new route estimation. The performance evaluation shows our solutions' ability to minimize traffic jams and improve mobility, with a low communication overhead compared to state-of-the-art solutions.